The Relationship Between Academic Values ​​of Bachelor of Cosmetology Education and Career Success in the Beauty Industry - Lela Alifianur Fadilah; Dindy Sinta Megasari; M.A. Hanny Ferry Fernanda; Nieke Andina Wijaya (Adornata : Ethnobeauty and Wellness Journal, 2025)
This research aims to 1) Knowing the career success that has been achieved by graduates in 2023 S1 Cosmetology Education. 2) Knowing the contribution of graduates' GPA in achieving career success in the beauty industry. 3) To find out the relationship between the academic value of graduates in 2023 S1 cosmetology education to career success in the beauty industry. The research approach uses quantitative with a correlation research method that is carried out online without limited time and place by utilizing digital platforms as a means of data collection, the subjects in this study are 35 graduates in 2023 S1 Cosmetology Education. The data collection technique used a likert scale with a questionnaire questionnaire instrument. The data analysis technique used the mean value and Pearson correlation at SPSS 25. The results of the study found that: (1) there are 46% of graduates with the most salary/income category 3 in 2021, which ranges from 5-10 million, compared to category 1 (23%), category 2 (14%) and category 4 (17%). (2) Academic scores based on GPAs obtained by graduates show that 77% of graduates get a GPA of category 4, which ranges from 3.51-4.00 and the remaining 23% get a GPA of category 3, which ranges from 3.00-3.50. (3) there was a very significant relationship between academic grades and graduate career success, with a Pearson correlation of 0.794 (p value = 0.000). Shows that academic grades are significantly related to the success of a graduate's career in the beauty industry. Suggestions for further research to further research related to the development of the beauty industry, new technologies, and other factors that affect the success of graduates' careers.